Analisis Logam Berat pada Air Waduk Tunggu Pampang - Andis Sugrani; Muh. Rivai Malik; Fitriana Fitriana; Nuramaniyah Taufiq (Poltekkes Kemenkes Padang, 2023)
Water pollution is the entry or inclusion of living things, substances, energy and or other components into the water by human activities, so that the quality of the water drops to a level that causes the water to not function according to its designation. The Waiting Pampang Reservoir is open and accessible to the general public including fishing activities. The consequences if the water in this reservoir contains heavy metals will also accumulate in marine biota (fish). If these fish are consumed, it will have an impact on human health. This study aims to determine heavy metals in the waiting reservoir water in the city of Makassar. Analysis of the metal content of Hg,Pb,Cu and Cd in the sample using the Atomic Absorption Spectrophotometry (AAS) calibration curve method. Before the samples were analyzed in SSA, sample preparation was carried out using the wet destruction method. The results of the analysis with SSA showed that the heavy metals in the sample had exceeded the threshold set by the 2011 Minister of Health, namely mercury (Hg) of 0.015, lead (Pb) of 0.08, copper (Cu) of 0.05 and cadmium (Cd) of 0. ,05. In conclusion, the water sample of the Waiting Pampang Reservoir has exceeded the maximum limit for heavy metal contamination in water that has been set by the government. It is recommended to add more sampling points to reservoir water.